New NBIA subtype: Genetic, clinical, pathologic, and radiographic features of MPAN - Hogarth, Penelope (Lippincott Williams & Wilkins, 2013)
OBJECTIVE: To assess the frequency of mutations in C19orf12 in the greater neurodegeneration with brain iron accumulation (NBIA) population and further characterize the associated phenotype. METHODS: Samples from 161 individuals with idiopathic NBIA were screened, and C19orf12 mutations were identified in 23 subjects. Direct examinations were completed on 8 of these individuals, and medical records were reviewed on all 23. Histochemical and immunohistochemical studies were performed on brain tissue from one deceased subject. RESULTS: A variety of mutations were detected in this cohort, in addition to the Eastern European founder mutation described previously. The characteristic clinical features of mitochondrial membrane protein-associated neurodegeneration (MPAN) across all age groups include cognitive decline progressing to dementia, prominent neuropsychiatric abnormalities, and a motor neuronopathy. A distinctive pattern of brain iron accumulation is universal. Neuropathologic studies revealed neuronal loss, widespread iron deposits, and eosinophilic spheroidal structures in the basal ganglia. Lewy neurites were present in the globus pallidus, and Lewy bodies and neurites were widespread in other areas of the corpus striatum and midbrain structures. CONCLUSIONS: MPAN is caused by mutations in C19orf12 leading to NBIA and prominent, widespread Lewy body pathology. The clinical phenotype is recognizable and distinctive, and joins pantothenate kinase–associated neurodegeneration and PLA2G6-associated neurodegeneration as one of the major forms of NBIA.